Implementation of Student Management at Islamic Senior High Schools and 21-Century Learning - Muin, Abdul; Juhji, Juhji; Suedah, Suedah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to describe the implementation of student management in Islamic Senior High Schools (Madrasah Aliyah Negeri). This research was conducted at Madrasah Aliyah Negeri (MAN) 1 Serang as one of the State Madrasah Aliyah in Banten Province. A descriptive qualitative approach was used as the method in this study. The data were collected through three techniques from Miles and Huberman: observation, interview, and documentation. Direct interviews were conducted with the principal, vice-principal for curriculum, vice-principal for student affairs, and teachers as informants. Study data were analyzed using three stages: reducing data, presenting data, and drawing conclusions. The study findings describe that the implementation of student management in the school is exemplary. This study concludes that student management that has been implemented is optimal in supporting 21st-century learning. The research findings recommend that student management be implemented based on moral nature.